Accuracy of a ground-coupled antenna based non-contact method for detecting the integrity of lining contours - Ruilang Cao; Yanqing Yang; Yujie Wang; Xingsong Sun (International Journal of Distributed Sensor Networks)
Accurate detection of the lining contours is important for the evaluation of working condition and service life of the underground structures. A 1:1 test model was constructed to elucidate the accuracy of the non-contact detection of the lining profile with a ground-coupled antenna. In addition, the accuracy at various detection distances was qualitatively and quantitatively analyzed. At detection distances below 80 mm, it was found that a radar scanning map with well-defined lining contours could be obtained when gain processing techniques were applied to the measurement signal. As the detection distance is above 160 mm, the measured signal must be processed with horizontal background removal and vertical filter gain processing. In addition, when the detected values with large errors were corrected using the functional relationship between the contact and non-contact detection values, this effectively improved the detection accuracy to 92.05% at a detection distance of 160 mm. Based on the results of this study, the detection precision and non-contact detection distance were sufficient to satisfy the requirements for typical engineering applications. Considering the high accuracy and easy operability, the non-contact coupled antenna detection method is likely to be the best option to evaluate the lining contours in underground engineering.